Development of Phage Cocktails to Treat E. coli Catheter-Associated Urinary Tract Infection and Associated Biofilms - Sanchez, Belkys C.; Heckmann, Emmaline R.; Green, Sabrina I.; Clark, Justin R.; Kaplan, Heidi B.; Ramig, Robert F.; Muldrew, Kenneth L.; Hines-Munson, Casey; Skelton, Felicia; Trautner, Barbara W.; Maresso, Anthony W. (Frontiers in Microbiology, 2022)
High rates of antimicrobial resistance and formation of biofilms makes treatment of Escherichia coli catheter-associated urinary tract infections (CAUTI) particularly challenging. CAUTI affect 1 million patients per year in the US and are associated with morbidity and mortality, particularly as an etiology for sepsis. Phage have been proposed as a potential therapeutic option. Here, we report the development of phage cocktails that lyse contemporary E. coli strains isolated from the urine of patients with spinal cord injury (SCI) and display strong biofilm-forming properties. We characterized E. coli phage against biofilms in two in vitro CAUTI models. Biofilm viability was measured by an MTT assay that determines cell metabolic activity and by quantification of colony forming units. Nine phage decreased cell viability by >80% when added individually to biofilms of two E. coli strains in human urine. A phage cocktail comprising six phage lyses 82% of the strains in our E. coli library and is highly effective against young and old biofilms and against biofilms on silicon catheter materials. Using antibiotics together with our phage cocktail prevented or decreased emergence of E. coli resistant to phage in human urine. We created an anti-biofilm phage cocktail with broad host range against E. coli strains isolated from urine. These phage cocktails may have therapeutic potential against CAUTI.